Struktura oraz poziom kredytów gospodarstw rolniczych w zależności od zadłużenia i siły ekonomicznej - Mądra, Magdalena; Stola, Emilia (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The paper presents analysis on credits and loans used in financings the activity of agricultural farms. The empirical research is based on data collected under Farm Accountancy Data Network for the 2005. The aim of the paper is to determine the dependences among the level of debts and the European Unit Size of the agricultural farms depending on committed credits and loans. The results show the relation to the repayment security of the liabilities in farms and the sums of credits and loans counted per one hectare of cropland area. Farms with the highest level of debts were characterized with the diversification of the committed financing resources together with enlarged participation of the outside capital. The economically weaker farms (with a lower ESU) possessed higher participation of the short-term liabilities in the capital structure. It is connected with a reasonable financing strategy. Farms with the highest debts level were diversifying loan capital structure by maintaining higher participation of long-term financing resources, which is rational behaviour